Influence of Classical Novels and Improvisations of the Modern Novel: An Intertextual Study (International Journal of Food and Nutritional Sciences, 2023)
This article explores the influences of classical novels on the development of the modern novel as well as how contemporary writers modernize classical novels to suit today’s issues. Using a cross-cultural framework and intertextuality, the study starts from five fundamental areas: (1) narrative voice and interiority, (2) time, memory, and temporality, (3) intertextuality and metafiction, (4) realism, social critique, and the moral complexity of a society, and (5) hybridity and cross-cultural translation. Through a comparative approach, the study traces the evolution from the canonical framework of Don Quixote, Pride and Prejudice, Great Expectations, and Moby-Dick to contemporary and postmodern novels like Joyce’s Ulysses, Calvino’s If on a Winter's Night a Traveler, Garcia Marquez's One Hundred Years of Solitude, Morrison’s Beloved, Rushdie’s Midnight's Children, and Murakami's The Wind-Up Bird Chronicle. The study demonstrated that modern writers are able to improvise, while classical forms offer enduring scaffolds which include narrative depth, social critique, and structural scaffolds. The implications the study brings forth can be overshadowed by its greater contribution to literary pedagogy, translation studies, and readership in the context of globalization and the digital world. The study also provides a scope for further scholarly exploration of the modern and classical intersection.